Editorial: what editors welcome - Jankun, Jerzy; Redfern, Roberta; Sabharwal, Arjun (Translation: The University of Toledo Journal of Medical Sciences, 2018)
Translation; The University of Toledo Journal of Medical Sci- ences, online journal, launched a few years ago by UT, is accepting again papers in all aspects of medical sciences in four different categories.